2012
DOI: 10.5248/118.383
|View full text |Cite
|
Sign up to set email alerts
|

Geastrum species from the Amazon Forest, Brazil

Abstract: Six Geastrum species are reported from the Amazon forest: G. entomophilum, G. fimbriatum, G. javanicum, G. lageniforme, G. lilloi, and G. saccatum. Geastrum javanicum and G. lilloi represent first records from Brazil. Descriptions and illustrations of the species and SEM images of microstructures are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…The phylogenetic tree (Fig. 1) based on ITS, nrLSU, and atp6 showed that Geastrum is a multilineage genus, which is consistent with previous studies (Lloyd, 1902(Lloyd, , 1907Sunhede, 1989;Douanla et al, 2005;Kirk et al, 2008;Leite et al, 2011;Kasuya et al, 2012b;Jeppson et al, 2013;Zamora et al, 2013Zamora et al, , 2014aZamora et al, , 2014bZamora et al, , 2015Accioly et al, 2019). Elsewhere, sect.…”
Section: Comentssupporting
confidence: 88%
See 1 more Smart Citation
“…The phylogenetic tree (Fig. 1) based on ITS, nrLSU, and atp6 showed that Geastrum is a multilineage genus, which is consistent with previous studies (Lloyd, 1902(Lloyd, , 1907Sunhede, 1989;Douanla et al, 2005;Kirk et al, 2008;Leite et al, 2011;Kasuya et al, 2012b;Jeppson et al, 2013;Zamora et al, 2013Zamora et al, , 2014aZamora et al, , 2014bZamora et al, , 2015Accioly et al, 2019). Elsewhere, sect.…”
Section: Comentssupporting
confidence: 88%
“…Differs from G. fimbriatum Fr. by smaller basidiospores, fibrillose peristome and rhizomorphs covered with narrow prismatic crystals (Leite et al, 2011). Also differs from G. yanshanense by the light grayish orange pseudoparenchymatous layer (yellowish brown in G. yanshanense), and the larger basidiospores (2.8-3.3 μm in G. yanshanense) (Zhou et al, 2022).…”
mentioning
confidence: 99%
“…Distribution.-Although this taxon is widely known in Brazil: from Rio Grande do Sul (Rick, 1961;Sobestiansky, 2005;Cortez & al., 2008b), Paraná (De Meijer, 2006), São Paulo (Sydow & Sydow, 1907;Bononi & al., 1984;Baseia & al., 2003), Pernambuco (Kimbrough & al., 1994(Kimbrough & al., -1995Baseia & al., 2003;Trierveiler-Pereira & al., 2011) Rio Grande do Norte (Leite & Baseia, 2007), Bahia (TrierveilerPereira & al., 2009), Amazonas (Hennings, 1904a;Cabral & al., 2014b), Pará (Leite & al., 2011), Paraíba (Sousa & al., 2014b), this is the first record from Minas Gerais.…”
Section: Earthstars From Minas Geraismentioning
confidence: 99%
“…In Brazil, Geastrum fimbriatum has been reported from: Bahia (Trierveiler-Pereira & al., 2009), Paraíba (Trierveiler-Pereira & al., 2011, Pará (Leite & al., 2011;Trierveiler-Pereira & al., 2011), Pernambuco (Leite & al., 2007a;Trierveiler-Pereira & al., 2011), Rio de Janeiro (Berkeley & Cooke, 1876;Hennings, 1904b;Saccardo, 1888), Rio Grande do Norte (Sousa & al., 2014c), and Rio Grande do Sul (Rick, 1961;Lazarotto & al., 2014).…”
Section: Earthstars From Minas Geraismentioning
confidence: 99%
See 1 more Smart Citation